HYBRID ELECTRIC VEHICLES (HEV)- DC MOTOR COUPLE THREE PHASE INDUCTION MOTOR FOR AUTOMOTIVE APPLICATIONS - Zulkarnain Lubis (Prosiding Seminar Nasional Teknik UISU (SEMNASTEK), 2022)
An electric vehicle control system controls motor response based upon monitored vehicle characteristics to provide consistent vehicle performance under a variety of conditions for a given accelerator manipulation. With emphasis on a cleaner environment and efficient operation, vehicles today rely more and more heavily on electrical power generation for success. With the oil price shocks of the past few decades, as well as an increasing awareness of the emissions of air pollutants and greenhouse gases from cars and trucks, the interest to investigate alternative vehicle propulsion systems has grown. This challenge of fuel economy standards is promoting optimised and sometimes novel vehicle power automotive architectures, which combine the traditional internal combustion engine (ICE) with various forms of electric drives. The different types of the hybrid electric vehicles (HEV) are real competitors of the classical ICE driven cars. The controller of induction motor (IM) is designed based on input-output feedback linearization technique. It allows greater electrical generation capacity and the fuel economy and emissions benefits of hybrid electric automotive propulsion. Finally, a typical series hybrid electric vehicle is modelled and investigated. Control system integrated starter dc motor couple three phase induction motor for automotive applications. Various tests, such as acceleration traversing ramp, and fuel consumption and emission are performed on the proposed model of 3 phase induction motor coupler dc motor in electric hybrid vehicles drive.